Analysis of Deprivations Suffered by Children Under Five in Benin - Fawaz A. Adéchinan Aminou; Pam Zahonogo (Publisher of Widyagama University of Malang (UWG Press), 2019)
Children are seriously affected by poverty and suffer particular deprivations. In addition, their situation is most of the time ignored in the strategies devoted to tackling poverty. This study examined the multidimensional poverty of children under five in Benin by identifying its determinants. It used the data from the demographic and health surveys in Benin from 2011-2012 and adopted the approach by Alkire & Foster (2011) to generate multidimensional poverty profiles of children. The weightings of the dimensions were generated by multiple correspondence analysis. The GLM and Logit models were used to identify the driving factors of child deprivation. Findings indicate that 54 percent of children were multidimensionally poor when the poverty line k = 1 against 32 percent of poor children when k = 3. Nutrition and sanitation dimensions had the highest relative contributions of 41.12 and 28.77 percent respectively to the global multidimensional poverty index. JEL Classification: D63, I32, O10